A comprehensive review on ultrathin, multi-functionalized, and smart graphene and graphene-based composite protective coatings. (March 2023) - Ren, Siming; Cui, Mingjun; Liu, Chengbao; Wang, Liping
Abstract: A new generation of ultrathin, functional, self-repairing graphene-based coatings is emerging. Such coatings have excellent potential for corrosion protection owing to the superior mechanical properties, high specific aspect ratio and impermeability of graphene. This paper summarizes the barrier mechanisms, existing questions, and limitations pertaining to ultrathin graphene coatings. The main factors affecting the corrosion resistance of graphene-based composite coatings, including their orientation, dispersion, size, content, and conductivity, are systematically discussed. The advantages and self-repairing mechanisms of smart graphene-based composite coatings are also highlighted. The challenges associated with graphene and graphene-based composite coatings for metal protection are discussed.